Oracle application server 10g essentials - Greenwald, Rick (O'Reilly Media, Inc., 2004)
The new Oracle Application Server offers a wide range of functionality, including Java runtime and development tools, portal development tools, business intelligence, single sign-on identify management, and much more. It's so powerful and complex, in fact, that many people who use the product (or are considering using it) are familiar with only a portion of the entire range of its capabilities. The choices can be overwhelming. Few people grasp how the larger issues--such as the interplay between components or the various architectural choices in the product--play out in the Oracle Application Server. This new guide provides the perfect introduction to the Oracle Application Server for users of any level. Regardless of which of the server's capabilities you use, you'll benefit from this tightly focused, all-in-one technical overview. It's written for anyone who is concerned with using and managing web servers, doing Java development and deployment, using Oracle's own tools--like Forms and Reports, using or developing for Oracle Portal, or those who use and administer business intelligence, mobile or integration software. Divided into three concise sections, the book covers server basics, core components, and server functionality. The book leads with the history of Oracle Application Server, its architecture, management, standards, and third-party support for languages and tools such as Java, Perl, and HTTP. The next section covers Oracle's web server, containers for Java web caching, and the server's security features. And finally, the book discusses HTML development, Java development, and Oracle development. Although the book refers mainly to Oracle Application Server 10g, the authors also describe features in earlier product releases where necessary, particularly Oracle9i Application Server. More comprehensible than a large reference and more detailed than a primer, the book provides a foundation for understanding and using Oracle Application Server effectively and efficiently. Readers concentrate on the most important issues and components of the server, focusing primarily on principles rather than syntax. Designed to be the ideal first OracleAS book, Oracle Application Server 10g Essentials offers Oracle application developers and administrators everything they need to know about this powerful server.